The relationship between brucellosis and vitamin D - Behice Kurtaran; Ozay Akyildiz; Aslihan Candevir Ulu; Seza Ayse Inal; Suheyla Komur; Gulsah Seydaoglu; Yusuf Kemal Arslan; Akgun Yaman; Filiz Kibar; Hasan Salih Zeki Aksu; Yesim Tasova (Journal of Infection in Developing Countries)
Introduction: This study was aimed to determine the relationship between vitamin D and soluble vitamin D receptor (VDR) levels and brucellosis, a common infection in Turkey, in which the cellular immune system is important in the course of the disease. Methodology: Patients who had been followed up in the Department of Infectious Diseases and Clinical Microbiology of Cukurova University Medical Faculty, having been diagnosed with brucellosis and who had no brucellosis treatment before, were enrolled in the study along with healthy controls. The participants’ vitamin D and soluble VDR values were recorded. Laboratory parameters of patients and controls, clinical findings, and disease course of brucellosis patients were also noted. Results: The mean age of the 86 brucellosis patients, of whom 38 (44.2%) were males and 48 (55.8%) were females, was 40.9 ± 18.4 years. Complicated course of brucellosis rate was found to be 29.1%. Vitamin D and VDR levels were lower in brucellosis patients at the time of diagnosis compared to control group. For males, vitamin D and VDR levels were higher in the control group than in the patient group. In males, VDR levels were higher than in females. A significant difference was not found between clinical forms of the disease and vitamin D and VDR levels. Conclusions: Vitamin D and VDR levels were shown to be significantly lower in brucellosis patients before treatment compared to the control group. These results suggest that vitamin D could be involved in the pathogenesis of the disease.